Methodology development for routine estimation of chlorpropham in commercial potato stores - Waqar A. Khan; H.J. Duncan; Ahmad K. Baloch; Geraldine McGowan (Czech Journal of Food Sciences, 2012)
Chlorpropham is employed worldwide as an anti-sprout chemical to the harvested potato tubers during storage. A simple and precise analytical technique is developed for routine estimation of the sprout suppressant from a large number of potato samples supplied from commercial stores demanding quick analysis. Chlorpropham is extracted completely from potato tubers by intelligent reflux extraction followed by quantification using GC-FID (Gas Chromatography-Flame Ionization Detector) equipment. In this article, the performance of the technique is compared with the lengthy extraction/cleanup process, and the results are validated as per one-way analysis of variance. The recommended technique is found to offer rapid, accurate, and reliable analytical results with ease in handling a large number of samples constituting a wide range of residual chlorpropham levels often found in a complex structural commercial potato stores.